Transient Receptor Potential Vanilloid 1 Modulates Central Inflammation in Multiple Sclerosis - Stampanoni Bassi, Mario; Gentile, Antonietta; Iezzi, Ennio; Zagaglia, Sara; Musella, Alessandra; Simonelli, Ilaria; Gilio, Luana; Furlan, Roberto; Finardi, Annamaria; Marfia, Girolama A.; Guadalupi, Livia; Bullitta, Silvia; et al. (Frontiers in Neurology, 2019)
Introduction: Disease course of multiple sclerosis (MS) is negatively influenced by proinflammatory molecules released by activated T and B lymphocytes and local immune cells. The endovanilloid system plays different physiological functions, and preclinical data suggest that transient receptor potential vanilloid type 1 (TRPV1) could modulate neuroinflammation in this disorder. Methods: The effect of TRPV1 activation on the release of two main proinflammatory cytokines, tumor necrosis factor (TNF) and interleukin (IL)-6, was explored in activated microglial cells. Furthermore, in a group of 132 MS patients, the association between the cerebrospinal fluid (CSF) levels of TNF and IL-6 and a single nucleotide polymorphisms (SNP) influencing TRPV1 protein expression and function (rs222747) was assessed. Results: In in vitro experiments, TRPV1 stimulation by capsaicin significantly reduced TNF and IL-6 release by activated microglial cells. Moreover, the anti-inflammatory effect of TRPV1 activation was confirmed by another TRPV1 agonist, the resiniferatoxin (RTX), whose effects were significantly inhibited by the TRPV1 antagonist, 5-iodoresiniferatoxin (5-IRTX). Vice versa, BV2 pre-treatment with 5-IRTX increased the inflammatory response induced by LPS. Moreover, in MS patients, a significant association emerged between TRPV1 SNP rs222747 and CSF TNF levels. In particular, the presence of a G allele, known to result in increased TRPV1 protein expression and function, was associated to lower CSF levels of TNF. Conclusions: Our results indicate that TRPV1 influences central inflammation in MS by regulating cytokine release by activated microglial cells. The modulation of the endovanilloid system may represent a useful approach to contrast neuroinflammation in MS.